Expression Analysis of OsVTC1-1 Gene in Ascorbic Acid Biosynthesis Pathway during Rice Blast Fungus Infection - Loedkunchotiphat, Kanyanat; Longya, Apinya; Jantasuriyarat, Chatchawan; Kate-Ngam, Sureeporn (Thai Journal of Science and Technology, 2018)
Abstract Rice (Oryza sativa) is an important staple food crop in the world especially in Asia. Nowadays, the rice yields in Thailand have lower productivity due to many factors such as fungal diseases. Magnaporthe oryzae also known as a rice blast fungus, is an important plant pathogen that causes lesions in all parts of the plant. Ascorbic acid (AsA) or vitamin C is a powerful antioxidant and plays an important role in the plant defensive response. Previous study showed that GDP-D-mannose pyrophosphorylase (GMP or VTC1) is a key gene in ascorbic acid synthesis pathway. In this experiment, we aim to study the expression level of OsVTC1-1 gene during rice blast fungus infection. Two isolates of rice blast fungus that can and cannot infect Jao Hom Nin were used. Leave samples were collected at 0, 6, 12, 24 and 36 hours after inoculation. Then, the expression level of OsVTC1-1 gene was examined using semi-quantitative RT-PCR. The results showed that OsVTC1-1 gene was expressed at the highest level at 12 hours after inoculation and decreased to normal levels after 12 hours. The pattern of this gene expression showed the same in both resistance and susceptible reaction, which indicated that AsA may play a role in defense response upon fungal infection. OsVTC1-1 gene was cloned to study gene structure and genetic relationship among plant species. This gene consists of 1,086 bp and encodes 362 amino acid residues. The phylogenetic tree revealed that OsVTC1-1 was grouped into two groups, monocotyledon and dicotyledon. Our results suggested that OsVTC1-1 is conserved throughout plant kingdom and may play an important role in rice blast fungus defense response. Keywords: ascorbic acid; blast disease; L-galactose pathway; rice; vitamin C